Students’ Perception Of Using Canva In Paragraph Writing Class - Rokhmatin, Siti Elvyn; Lindawati, Rini; Ganinda, Nurhayati (Philosophiamundi, 2024)
This study aims to find out the students’ perceptions of the Canva application in the Paragraph Writing class and the students’ perceptions when working on projects in the Paragraph Writing class. The research was conducted in the English Education Department at Majapahit Islamic University. This study seeks the students’ perceptions of using the Canva application in the learning process and their experiences in project-based learning tasks. This study used a descriptive qualitative method. The researcher used Focus Group Discussions (FGD) as the data collection technique. Focus Group Discussion conducted by researchers with a group of people over time. This group of people was not interviewed separately, but together in the form of a forum. In this research, two findings was found out students’ perceptions in the Paragraph Writing class and students’ projects in the Paragraph Writing class. First, all students gave positive perceptions regarding their understanding of the learning in the class using the Canva application as the media. Students also stated they benefitted from the advantages of using the Canva application in learning. Second, the Canva application helped students complete their projects, although challenges and obstacles arose when students directly applied Canva as an assisting medium. In conclusion, the learner’s perception of the Canva application in the Paragraph Writing class was positive because Canva helps students understand the learning material better. The project also had positive results because it was easier for students to complete the project of creating a digital fiction book. Through this research, the researcher hopes that in future research the results of this study could be used in compiling further research designs that are relevant and more varied